A flying start? Long term consequences of maternal time investments in children during their first year of life - Pedro Carneiro; Katrine V. Loken; Kjell G. Salvanes (Institute for the Study of Labor (IZA), 2010)
We study the impact on children of increasing the time that the mother spends with her child in the first year by exploiting a reform that increased paid and unpaid maternity leave in Norway. The reform increased maternal leave on average by 4 months and family income was unaffected. The increased time with the child led to a 2.7 percentage points decline in high school dropout. For mothers with low education we find a 5.2 percentage points decline. The effect is also especially large for children of mothers who, prior to the reform, would take very low levels of unpaid leave.
Keywords: J13; 330; adult outcomes; time with mother; maternity leave